2019
DOI: 10.11113/matematika.v35.n3.1130
|View full text |Cite
|
Sign up to set email alerts
|

Co-prime Probability for Nonabelian Metabelian Groups of Order Less than 24 and Their Related Graphs

Abstract: Let G be a finite group. The probability of a random pair of elements in G are said to be co-prime when the greatest common divisor of order x and y, where x and y in G, is equal to one. Meanwhile the co-prime graph of a group is defined as a graph whose vertices are elements of G and two distinct vertices are adjacent if and only if the greatest common divisor of order x and y is equal to one. In this paper, the co-prime probability and its graph such as the type and the properties of the graph are determined. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Zulkifli and Mohd Ali [9] conducted an extensive study in this part which they determined the coprime probability for nonabelian metabelian groups of order less than 24. Here, it may be discovered that if G has the same order, then the coprime probability of nonabelian metabelian groups of order less than 24 are the same.…”
Section: Definition 2: [4] Noncoprime Graphmentioning
confidence: 99%
“…Zulkifli and Mohd Ali [9] conducted an extensive study in this part which they determined the coprime probability for nonabelian metabelian groups of order less than 24. Here, it may be discovered that if G has the same order, then the coprime probability of nonabelian metabelian groups of order less than 24 are the same.…”
Section: Definition 2: [4] Noncoprime Graphmentioning
confidence: 99%
“…In the paper, the author determined the types and some properties of the graph and the results are stated in Section 2 since the Their Associated Graph Properties results will be used throughout this research. Recently, Zulkifli and Mohd Ali in [4] and [5] continued the research of coprime graph done by Ma et al [2] but the scope of group was mainly on the nonabelian metabelian groups of order less than 24 and order 24, respectively. Both papers were targeted on finding the types of graphs, the domination number, the independence number, and the number of edges that can be obtained within a group.…”
Section: Definition 1: [2] Coprime Graph Of a Groupmentioning
confidence: 99%
“…and n is odd are discussed. Later, Zulkifli and Mohd Ali [4] made an extensive research on the coprime probability in which the scope of the group is on the nonabelian metabelian groups of order less than 24. The results showed that the coprime probability of dihedral groups or -groups p are the same when G has the same order.…”
Section: Definition 1: [2] Coprime Graph Of a Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found the probability for p-groups and for some dihedral groups. Later in 2019, Zulkifli and Mohd Ali in [21] and [20] made an extensive research on the coprime probability in which the scope of the group is on the nonabelian metabelian groups of order less than 24 and order 24, respectively.…”
Section: Introductionmentioning
confidence: 99%